Respostas
respondido por:
2
x+3y=6
-x+6y=12
x-x+3y+6y=6+12
0+9y=18
y=18/9
y=2
x+3y=6
x+3.2=6
x=6-6
x=0
-x+6y=12
x-x+3y+6y=6+12
0+9y=18
y=18/9
y=2
x+3y=6
x+3.2=6
x=6-6
x=0
respondido por:
0
x+3y=6
-x+6y=12
podemos anular o x.
3y+6y=18 fazendo a soma.
9y=18
y=2
x+3*2=6
x=-6+6
x=0
R:y=2
x=0
-x+6y=12
podemos anular o x.
3y+6y=18 fazendo a soma.
9y=18
y=2
x+3*2=6
x=-6+6
x=0
R:y=2
x=0
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás